ADAB PERNIKAHAN PERSPEKTIF HUKUM ISLAM MENURUT MUHAMMAD NASHIRUDDIN AL ALBANI - Ipandang Ipandang (MUADDIB Jurnal Kependidikan dan Keislaman, 2020)
Islam teach about the importance of marriage, because every individual is created in pairs. In carrying out a marriage, there are many kinds of wedding ceremonies, customs and wedding processions in Indonesia, so the role of religion is very important in framing this culture, Islam is the religion of rahmatan lil'alamin. a culture that is not allowed to live freely but needs to provide understanding and is also packed with the values of Islamic religious teachings, because religion is a source of value in every aspect of life, including culture, because culture that does not involve the religious aspects contained therein will make a culture that is misleading, so should a culture that is framed by Islamic teachings then it will give birth to a culture that has Islamic values in it. One of them is marriage customs which are in accordance with Islamic law. Muhammad Nashiruddin Al Albani is one of the figures who is very focused on discussing manners in marriage which is later recorded in his book entitled Adab Az-Zifaf and also Adab Az-Zafaf Fi As-Sunnah Al Muthahharah. In this article, we will discuss some of his thoughts regarding marriage manners